THE PREVENTION OF IRON DEFICIENCY IN INFANTS - N. А. Belykh (Медицинский вестник Юга России, 2015)
Purpose: to evaluate the different methods of prevention of iron deficiency anemia in breast-fed infants.Materials and methods: studied questionnaires of 948 lactating mothers, determined the hemoglobin level in their infants, the serum ferritin and serum iron level, the total iron binding capacity of serum (n=96), the breast milk iron concentration (n=88).Results: the median of breast milk iron concentration was independent of iron supplementation in lactating mother’s (2.1 μmol/L vs. 3.4 μmol/L, р=0.16). Iron status was better in breast-fed infants with iron supplementation.Summary: sron supplementation with of 1 mg/kg, starting at 4 months of age during 2 months in exclusively breast-fed infants is more effective compared to iron-containing vitamin and mineral complexes intake in lactating mothers.